Role of micronutrients in the modulation of immune system and platelet activating factor in patients with COVID-19; a narrative review - Doaei, Saeid; Mardi, Afrouz; Zare, Maryam (Frontiers in Nutrition, 2023)
Background: Dietary micronutrients may play important roles in the improvement of the immune responses against SARS-COV-2. This study aimed to assess the effect of micronutrients on platelet activating factor (PAF) and immunity with a special focus on the coronavirus disease 2019 (COVID-19).: All paper published in English on the effects of micronutrients including fat soluble vitamins, water soluble vitamins, and minerals on PAF, immunity, and COVID-19 were collected from online valid databases. Results: Vitamin A may modulate the expression of PAF-receptor gene in patients with COVID-19. Vitamin D may modulate inflammatory response through influencing PAF pathway. Vitamin E may improve COVID-19 related heart injuries by exert anti-PAF activities. Vitamin C status may have PAF related anti-inflammatory and micro-thrombotic effects in SARS-COV-2 patients. Furthermore, some trace elements such as copper, selenium, and iron may have key roles in strengthens immunity by inactivate PAF acetyl hydrolase. Conclusion: This narrative review study highlighted the importance of micronutrients in the improvement of immune function through modulation of PAF in patients with COVID-19.Further longitudinal studies are warranted.